HUBUNGAN ANTARA MOTIVASI INTRINSIK DENGAN PROKRASTINASI AKADEMIK SISWA SMA - Nur Damiyati, Adibah; Supriatna, Ecep; Finanto Ario Bangun, Mic (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to examine the relationship between intrinsic motivation and academic procrastination among high school students. Although academic procrastination is a common phenomenon, most previous studies have focused on university students, making research at the high school level still limited. This research employed a quantitative approach with a correlational method. The sample consisted of 163 eleventh-grade high school students selected through simple random sampling. The measurement instruments used were an intrinsic motivation scale and an academic procrastination scale. The intrinsic motivation scale consisted of 18 items, while the academic procrastination scale consisted of 19 items. Both instruments had been tested for validity and reliability, with item validity scores > 0.300 and Cronbach’s Alpha reliability coefficients of 0.898, respectively. Data analysis was conducted using Spearman’s Rho correlation with the assistance of SPSS 25 software.The results revealed a significant negative relationship between intrinsic motivation and academic procrastination, with a correlation coefficient of -0.762 and a significance value of p < 0.05. This means that the higher the students’ intrinsic motivation, the lower their tendency to delay academic tasks. These findings are expected to serve as a reference for high schools in developing learning strategies that can enhance students’ learning motivation to reduce academic procrastination behavior. ABSTRAK Penelitian ini bertujuan untuk menguji hubungan antara motivasi intrinsik dan prokrastinasi akademik pada siswa SMA. Meskipun prokrastinasi akademik merupakan fenomena umum, sebagian besar studi sebelumnya lebih berfokus pada mahasiswa, sehingga penelitian pada tingkat sekolah menengah masih terbatas. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Sampel dalam penelitian ini berjumlah 163 siswa kelas XI SMA yang dipilih dengan teknik simple random sampling. Alat ukur yang digunakan adalah skala motivasi intrinsik dan skala prokrastinasi akademik. Skala motivasi intrinsik terdiri dari 18 item, sedangkan skala prokrastinasi akademik terdiri dari 19 item. Kedua instrumen tersebut telah diuji validitas dan reliabilitasnya, dengan hasil validitas item > 0,300 dan reliabilitas Cronbach’s Alpha masing-masing sebesar 0,898. Analisis data dilakukan menggunakan korelasi Spearman-Rho dengan bantuan software SPSS 25. Hasil penelitian menunjukkan adanya hubungan negatif yang signifikan antara motivasi intrinsik dan prokrastinasi akademik, dengan nilai koefisien korelasi sebesar -0,762 dan nilai signifikansi (p < 0,05). Artinya, semakin tinggi motivasi intrinsik yang dimiliki siswa, maka semakin rendah kecenderungan mereka untuk menunda tugas-tugas akademik. Temuan ini diharapkan dapat menjadi acuan bagi pihak SMA dalam mengembangkan strategi pembelajaran yang mampu meningkatkan motivasi belajar siswa guna menekan perilaku prokrastinasi akademik.